Cardiac workup and monitoring in hospitalised children with COVID- 19. (2nd July 2020) - Fremed, Michael A.; Lytrivi, Irene D.; Liberman, Leonardo; Anderson, Brett R.; Barry, Oliver M.; Choudhury, Tarif A.; Chrisomalis-Dring, Sophia; Ferris, Anne; Glickstein, Julie S.; Krishnan, Usha; Levasseur, Stéphanie; Rosenzweig, Erika B.; et al.
Abstract: Approximately, 1.7 million individuals in the United States have been infected with SARS-CoV-2, the virus responsible for the novel coronavirus disease-2019 (COVID-19). This has disproportionately impacted adults, but many children have been infected and hospitalised as well. To date, there is not much information published addressing the cardiac workup and monitoring of children with COVID-19. Here, we share the approach to the cardiac workup and monitoring utilised at a large congenital heart centre in New York City, the epicentre of the COVID-19 pandemic in the United States.